New deltochiline (Coleoptera: Scarabaeidae: Scarabaeinae) taxa associated with hyrax dung in arid south western Namibia - Deschodt, Christian M.; Davis, Adrian L.v. (Zootaxa, 2018)
A survey of rock hyrax dung middens along the arid escarpment of southwest Namibia has filled a gap in the range shown by members of the Byrrhidium group of flightless dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) belonging to the tribe Deltochilini. The survey discovered a new genus and species, Ausmontins jacobsi new genus and species, and a further four new species in two previously described genera, Namakwanus kamfferi new species, Namakwanus minutus new species, Namaphilus nubibmontanus new species and Namaphilus tirasmontanus new species. They are described and illustrated in the present paper. This addition of new taxa raises the total complement of the Byrrhidium group to seven genera and 19 species. An updated key to all the known species is also provided. It is probable that further taxa await discovery.